2022
DOI: 10.3390/ijms23158080
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress Induces Cardiac Fibrosis in Obese Rats through Modulation of Transthyretin

Abstract: A proteomic approach was used to characterize potential mediators involved in the improvement in cardiac fibrosis observed with the administration of the mitochondrial antioxidant MitoQ in obese rats. Male Wistar rats were fed a standard diet (3.5% fat; CT) or a high-fat diet (35% fat; HFD) and treated with vehicle or MitoQ (200 μM) in drinking water for 7 weeks. Obesity modulated the expression of 33 proteins as compared with controls of the more than 1000 proteins identified. These include proteins related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The development of cardiac remodeling and dysfunction is often accompa-nied by increased levels of cardiac hypertrophy factors (such as ANP, BNP, and Myh7) [34] and fibrosis factors (such as CoL1 and CoL3) [35]. In this study, we observed that the cardiac dysfunction in obese rats was associated with exacerbated cardiac hypertrophy and fibrosis, which was consistent with previous findings by Daher [36] and Martinez [37]. Following SG, the cardiac dysfunction and fibrosis were significantly alleviated, providing further evidence for the cardiac protective effect of SG in obese rats.…”
Section: Discussionsupporting
confidence: 92%
“…The development of cardiac remodeling and dysfunction is often accompa-nied by increased levels of cardiac hypertrophy factors (such as ANP, BNP, and Myh7) [34] and fibrosis factors (such as CoL1 and CoL3) [35]. In this study, we observed that the cardiac dysfunction in obese rats was associated with exacerbated cardiac hypertrophy and fibrosis, which was consistent with previous findings by Daher [36] and Martinez [37]. Following SG, the cardiac dysfunction and fibrosis were significantly alleviated, providing further evidence for the cardiac protective effect of SG in obese rats.…”
Section: Discussionsupporting
confidence: 92%
“…Ye et al detected 132 DEPs in the BALF of CTD-ILD patients using an LC−MS proteomic method. Surfactant protein D (SP-D), a humoral molecule of the congenital immune system, was found (30,66), and Hant et al pointed out in their pathological studies that it reflected the status of pulmonary fibrosis and could be used as an alternative indicator to evaluate lung involvement (67). Meanwhile, multiple studies have found that increased SP-D is associated with ILD in patients with SSc, RA, and DM/PM using serum samples (32,67,68).…”
Section: Proteomics Studies In Other Subtypes Of Ctd-ildmentioning
confidence: 99%
“…Some proteomic studies have not been subdivided into subtypes of CTD-ILD, and the results are of great concern. For instance, cell adhesion molecule 1 (CADM1) was found to be downregulated in CTD-ILD ( 30 ). It has been suggested that it is a key adhesion receptor regulating human lung mast cells (HLMCs) and primary human lung fibroblasts ( 30 , 60 ).…”
Section: Proteomics Studies In Different Ctd-ild Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of functional cardiac alterations, transthyretin (TTR) was increased at cardiac and plasma levels in obese animals. Moreover, TTR induced profibrotic events and ER stress activation through mitochondrial oxidative stress in cardiac cells, suggesting a possible novel approach to TTR-related diseases [ 10 ].…”
mentioning
confidence: 99%